Knowledge of exclusive breastfeeding among primigravida mothers: A descriptive study - Aulia, Siti (Science Center Group, 2025)
Background: Exclusive breastfeeding is a key public health strategy for improving infant survival and promoting optimal growth and development. Breast milk provides complete nutrients and immunological protection that reduces the risk of infectious diseases and long-term health problems. Despite global recommendations for exclusive breastfeeding during the first six months of life, its implementation remains suboptimal in many settings. Maternal knowledge, particularly among primigravida mothers who experience pregnancy for the first time, is considered a critical factor influencing breastfeeding practices. Objective:To describe the level of knowledge regarding exclusive breastfeeding among primigravida mothers attending antenatal care services. Methods: A quantitative descriptive study was conducted in September 2025 in the working area of a Public Health Center (Puskesmas). The study involved 100 primigravida mothers attending antenatal care visits who were selected using consecutive sampling. Data were collected using a validated questionnaire consisting of 20 multiple-choice items covering the definition, benefits, duration, techniques, and barriers related to exclusive breastfeeding. Content validity was assessed by experts, and reliability testing showed a Cronbach’s alpha value above 0.7. Data were analyzed using univariate analysis to describe respondent characteristics and knowledge levels, which were categorized as good, moderate, or poor. Results: More than half of the respondents demonstrated good knowledge regarding exclusive breastfeeding (52%), while 38% had moderate knowledge and 10% had poor knowledge. Respondents correctly answered questions related to the definition of exclusive breastfeeding (90%), whereas knowledge regarding technical aspects such as breast milk storage and maternal benefits remained limited. Higher knowledge levels were more frequently observed among mothers with higher education (72%), employed mothers (65%), and those aged 20–30 years. Participation in antenatal maternal classes was also associated with a higher proportion of good knowledge. Conclusion: Primigravida mothers generally possess adequate knowledge of exclusive breastfeeding; however, disparities remain across educational level, employment status, age, and exposure to antenatal education. Strengthening antenatal health education programs and providing practical breastfeeding guidance are essential to improve maternal readiness and support the successful implementation of exclusive breastfeeding practices.